Apparent reflectance modeling for camouflage pattern comparison metrics. Issue 8 (24th May 2022) - Michaelchuck Jr., Edward; Ramsey, Scott; Mayo, Troy; Thompson, Sarah; Lambrakos, Samuel
Abstract : Camouflage patterns consist of specified complex patterning where the reflectance, as a function of wavelength, of each pattern segment is specified. Camouflage complexity establishes a need to determine camouflage pattern reflectance characteristics as a function of observer distance. The apparent reflectance spectrum, the combination of all wavelengths of light reflected from large sample sizes for a given standoff distance, can serve as an evaluation tool for camouflage fabrics. Apparent reflectance spectrum is based on far-field and statistical characteristics of camouflage patterns due to diffuse scattering properties of electromagnetic waves. This report describes modeling and simulation of apparent reflectance spectra to be adopted as a foundation for multiple metrics used in evaluating camouflage patterns in terms of their far-field characteristics over the visible and shortwave infrared wavelengths. This approach allows for direct, numerical suitability comparisons between various fabrics that can be used to optimize camouflage selection for various operational environments.